Evaluation of internal control systems over cash management :A case study of five compassion centres in Morogoro region - Njama, Geofrey Andrew (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Masters of Business Administration-Corporate Management (MBA-CM) of Mzumbe University